Direct synthesis of Ru3(BTC)2metal-organic framework on a Ti/TiO2NT platform for improved performance in the photoelectroreduction of CO2 - Irikura, Kallyni [UNESP]; Perini, João Angelo Lima [UNESP]; Flor, Jader Barbosa Silva [UNESP]; Frem, Regina Célia Galvão [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2021)
This work describes the use of a thin film of Ru3(BTC)2 metal-organic framework (MOF) deposited onto Ti/TiO2 nanotubes as a photocathode in CO2 reduction. This approach combines the advantages of the ruthenium MOF as a heterogeneous catalyst and as an agent for trapping CO2 on its active sites, resulting in an eco-friendly technology for photoelectrocatalysis and the photoconversion of CO2 to methanol in aqueous media. Morphological and crystallographic analyses showed that thin films of Ru3(BTC)2 MOF could be deposited homogeneously onto anatase TiO2 nanotubes, improving the photocurrent response of the electrode to on/off cycles of UV/Vis light illumination. Under optimized conditions, the Ti/TiO2NT-Ru3(BTC)2 electrode produced 314 μmol L-1 of methanol by photoelectrocatalysis after 3 h, which was 2.3-fold higher than obtained by a photocatalytic process. The results indicated that the construction of multifunctional materials, such as by the deposition of the porous crystalline Ru3(BTC)2 MOF onto Ti/TiO2 electrodes, can lead to a new generation of porous photoelectrocatalysts suitable for the capture of CO2 and its selective reduction to methanol.
Keywords: Carbon dioxide; Metal-organic framework; Photoelectrocatalytic reduction; Titanium dioxide nanotubes